Progress toward Pay Equity in State Governments?. (28th December 2017) - Lewis, Gregory B.; Boyd, Jonathan; Pathak, Rahul
Abstract: Are state governments fulfilling their responsibilities to be model employers of women and minorities? Using U.S. Census Bureau data on individual employees from 1980 to 2015, this article looks at how much progress state governments have made toward eliminating racial and gender pay differences. It examines whether differences in education, age/experience, citizenship, English ability, hours worked, and occupation explain the pay differences. Patterns and explanations vary substantially by group, but state governments are doing a better job than private firms of closing pay gaps on almost every measure .